2010
DOI: 10.1590/s1519-566x2010000600024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trichomes on attractiveness and ovipositional preference of Bemisia tabaci (Genn.) B biotype (Hemiptera: Aleyrodidae) on tomato genotypes

Abstract: -Brazil is one of the world's largest tomato producer, but considerable part of the production is lost due to the attack of Bemisia tabaci (Genn.) B biotype. Resistant germoplasm plants can be an important method for B. tabaci control in integrated pest management approaches. The attractiveness and ovipositional preference of B. tabaci for 17 tomato genotypes were evaluated in a free-choice test. Trials were set up in a randomized block design with ten replicates. Each replicate (one tomato plant per pot) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
5
40
1
2
Order By: Relevance
“…Studies of plant resistance to the vector B. tabaci have found that this phytophagous is affected mainly by the external/physical characteristics of the leaf surface, such as hairiness, glandular trichomes, leaf shape and cuticle thickness (Berlinger, 1986;Boiça et al, 2007;Oriani and Vendramim, 2010;Oriani et al, 2011). Resistance to B. tabaci and its relation to plant morphological traits has been well documented in other crops, such as tomato, cotton, and cassava (Bellotti and Arias, 2001;Boiça et al, 2007;Oriani and Vendramim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of plant resistance to the vector B. tabaci have found that this phytophagous is affected mainly by the external/physical characteristics of the leaf surface, such as hairiness, glandular trichomes, leaf shape and cuticle thickness (Berlinger, 1986;Boiça et al, 2007;Oriani and Vendramim, 2010;Oriani et al, 2011). Resistance to B. tabaci and its relation to plant morphological traits has been well documented in other crops, such as tomato, cotton, and cassava (Bellotti and Arias, 2001;Boiça et al, 2007;Oriani and Vendramim, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, glandular trichomes release exudates that are able to capture whiteflies (Muigai et al, 2002;Oriani and Vendramim, 2010;Oriani et al, 2011a). Furthermore, glandular trichomes also captured a great number of first-instar of D. davidsoni, which were trapped by the exudates released by these trichomes.…”
Section: Resultsmentioning
confidence: 99%
“…Four tomato genotypes were chosen based on differences in the densities and types of trichomes, levels of antixenosis for oviposition (Oriani and Vendramim, 2010;Oriani et al, 2011a) and levels of feeding non-preference and/or antibiosis-based resistance (Oriani et al, 2011b) to B. tabaci B biotype. The chosen genotypes were: i) NAV1062 (S. pimpinellifolium = L. pimpinellifolium) -low degree of antixenosis for oviposition, low degree of feeding non-preference and/or antibiosis, and high density of type V non-glandular trichomes; ii) LA1335 (S. pimpinellifolium) -low degree of antixenosis for oviposition, high degree of feeding non-preference and/ or antibiosis, and low density of type V non-glandular trichomes; iii) PI134418 (S. habrochaites f. glabratum = L. hirsutum f. glabratum) -high degree of antixenosis for oviposition, low degree of feeding non-preference and/or antibiosis, and high density of type IV glandular trichomes; and iv) IAC294 (S. habrochaites f. glabratum) -low degree of antixenosis for oviposition, low degree of feeding non-preference and/or antibiosis, and medium density of type IV glandular trichomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the trichomes are appendages that can affect the activity of insects mechanically by pilosity, depending on their density, hardness, and the length and shape of the trichomes, just as chemicals can affect the insects through the release of allelochemicals (Oriani;Vendramim, 2010). The gossypol glands are involved in the defense of cotton cultivars, and their presence and density are negatively associated with the abundance and performance of herbivores, and the damage caused by them (Summy;King, 1992).…”
Section: Introductionmentioning
confidence: 99%